2013
DOI: 10.1039/c3fd00034f
|View full text |Cite
|
Sign up to set email alerts
|

The effects of aircraft on climate and pollution. Part II: 20-year impacts of exhaust from all commercial aircraft worldwide treated individually at the subgrid scale

Abstract: This study examines the 20-year impacts of emissions from all commercial aircraft flights worldwide on climate, cloudiness, and atmospheric composition. Aircraft emissions from each individual flight worldwide were modeled to evolve from the subgrid to grid scale with the global model described and evaluated in Part I of this study. Simulations with and without aircraft emissions were run for 20 years. Aircraft emissions were found to be responsible for -6% of Arctic surface global warming to date, -1.3% of to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
41
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(46 citation statements)
references
References 24 publications
4
41
1
Order By: Relevance
“…It is notable that for the NASA ModelE2, there is a decrease in O 3 above ~ 10 km which is largest at 12 km. There is also a large decrease in O 3 for GATOR‐GCMOM above ~14 km which reaches nearly −35 ppb by 16 km; this decrease is caused by aviation‐induced upper‐tropospheric increases in stability that reduce the transport of ozone vertically to above the aircraft layer [ Jacobson et al ., ]. Finally, there is a decrease in O 3 above 11 km in GEOS‐CCM, but at 60–90°N and 40–90°S (Figure S1).…”
Section: Resultsmentioning
confidence: 99%
“…It is notable that for the NASA ModelE2, there is a decrease in O 3 above ~ 10 km which is largest at 12 km. There is also a large decrease in O 3 for GATOR‐GCMOM above ~14 km which reaches nearly −35 ppb by 16 km; this decrease is caused by aviation‐induced upper‐tropospheric increases in stability that reduce the transport of ozone vertically to above the aircraft layer [ Jacobson et al ., ]. Finally, there is a decrease in O 3 above 11 km in GEOS‐CCM, but at 60–90°N and 40–90°S (Figure S1).…”
Section: Resultsmentioning
confidence: 99%
“…Righi et al (2013) reported a cooling effect of similar magnitude by aviation sulfate aerosols as in this study. Simulations using GATOR-GCMOM (Gas, Aerosol, Transport, Radiation, General-Circulation, Mesoscale, and Ocean Model) (Jacobson et al, 2011(Jacobson et al, , 2013 found a warming effect. The treatment of aviation soot in the parameterization can also lead to very different conclusion of their impact.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, they cover a much larger area of environmental effects than WeCare. However, emissions effects on climate are frequently limited to CO 2 -emissions within the PARTNER consortium, except for their project 12 [159], which concentrated on the climate impact of aviation as such. Other projects, which investigate technological options (e.g., [160]), limited climate impact assessments to fuel use and hence CO 2 emissions.…”
Section: Discussionmentioning
confidence: 99%